Early-Pregnancy Vitamin D Deficiency and Risk of Preterm Birth Subtypes. Issue 2 (February 2015) - Bodnar, Lisa M.; Platt, Robert W.; Simhan, Hyagriv N.
Abstract : OBJECTIVE: To estimate the association between maternal 25-hydroxyvitamin D concentrations and risk of preterm birth subtypes. METHODS: We performed a case–cohort study using data and banked samples from patients at a teaching hospital in Pittsburgh, Pennsylvania. Eligible participants were women with a prenatal aneuploidy screening serum sample at or before 20 weeks of gestation who subsequently delivered a singleton, liveborn neonate. Of the 12, 861 eligible women, we selected 2, 327 at random as well as all remaining preterm birth cases for a total of 1, 126 cases. Serum 25-hydroxyvitamin D was measured using liquid chromatography–tandem mass spectrometry. Multivariable log-binomial regression models were used to estimate associations between maternal vitamin D status and preterm birth at 37 weeks of gestation (separately by spontaneous or indicated) and preterm birth at less than 34 weeks of gestation. RESULTS: The incidence of preterm birth at less than 37 weeks of gestation was 8.6% overall and 11.3%, 8.6%, and 7.3% among mothers with serum 25-hydroxyvitamin D less than 50, 50–74.9, and 75 nmol/L or greater, respectively ( P <.01). After adjustment for maternal race and ethnicity, prepregnancy body mass index, season, smoking, and other confounders, the risk of preterm birth at less than 37 weeks of gestation significantly decreased as 25-hydroxyvitamin D increased to approximately 90 nmol/L and then plateaued (test of nonlinearity P <.01). Results were similar when limiting to cases that were medically indicated or occurred spontaneously and cases occurring at less than 34 weeks of gestation. CONCLUSION: Our data support a protective association maternal vitamin D sufficiency and preterm birth that combined with extant epidemiologic data may provide justification for a randomized clinical trial of maternal vitamin D replacement or supplementation to prevent preterm birth. LEVEL OF EVIDENCE: II Abstract : Maternal vitamin D deficiency at or before 20 weeks of gestation is associated with a significant increase in the adjusted risk of all subtypes of preterm birth.Supplemental Digital Content is Available in the Text.